BECOMING KNOWLEDGE SOCIETIES: A Happiness Framework for Institutions of Higher Education in India - Nayar, Anupama (Journal of Dharma, 2019)
The transformation of Indian Higher Education Institutions (IHEIs) to knowledge societies require multiple coordinated interventions and actions on both the local and the global levels of institution administration, management, supply and demands of the economy and society. A vibrant knowledge society will not only require institution’s support to plan and amend practices but also require the engagement of all stakeholders and the ability of individuals and society to imbibe new ways of thinking, working, and acting. It is vital to chart a direction and an approach that is in alignment with the local context and culture. At the supply front, IHEIs should initiate intervention programmes to enhance human capital through investment in a Happiness Framework and a shift in the workplace culture that requires conscious measures of intervention, which will drive institutional effectiveness and improve student experiences. This happiness framework should be integral and reinforced, first as an induction-training programme, and practised as institutional culture. Individuals, who are thus, trained at the local level of institutions, while participating in the global labour market with their increased skills and competencies will drive the IHEIs towards a fully functioning knowledge-based society. A knowledge-based society thus built to generate, disseminate, and use knowledge to improve the standard of living and the quality of life of citizens in an ethical and sustainable way will certainly make happinessas its ultimate goal and will focus on happiness as a process to improve efficiency and efficacy of the work force.